2019
DOI: 10.1002/joec.12113
|View full text |Cite
|
Sign up to set email alerts
|

Using Direct Skills Teaching to Improve Job Skills for Persons With Disabilities

Abstract: This study evaluated whether a direct skills training (DST) approach for persons with disabilities can better prepare participants for job interviews. Twenty graduate students in a master's program in rehabilitation counseling at various agency internship sites were trained in a 4-session Presenting Qualifications curriculum based on DST administered to 126 participants in 20 group settings. Participants reported greater confidence and preparedness in the interview process, in answering difficult questions, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
(48 reference statements)
0
10
0
Order By: Relevance
“…A total of 87 individuals with psychiatric disabilities participated in Study 1, receiving the "Presenting Qualifications" intervention. The findings of 27 of the 87 participants were reported in an earlier study (Oursler et al, 2019). The earlier study reported data for people with various disabilities and did not provide analyses specifically for people with psychiatric disabilities.…”
Section: Participantsmentioning
confidence: 80%
See 1 more Smart Citation
“…A total of 87 individuals with psychiatric disabilities participated in Study 1, receiving the "Presenting Qualifications" intervention. The findings of 27 of the 87 participants were reported in an earlier study (Oursler et al, 2019). The earlier study reported data for people with various disabilities and did not provide analyses specifically for people with psychiatric disabilities.…”
Section: Participantsmentioning
confidence: 80%
“…This study implemented two curricula (“Presenting Qualifications” and “Conversing with Others”) among persons with psychiatric disorders who are receiving community mental health, vocational, or housing services. Both utilized DST as designed to help persons with psychiatric disabilities to communicate effectively to employers the skills that qualify them for a position (Oursler et al, 2019) or to engage in lunch time conversations with coworkers (Lu et al, 2020b). The study assessed the feasibility (i.e., acceptability and practicality) of the interventions in increasing perceived interview preparedness or in increasing perceived conversational ease with coworkers.…”
mentioning
confidence: 99%
“…This skill includes choosing topics, demonstrating interest in what others are saying (verbally and non-verbally), changing a topic, and concluding the conversation. This skill can extend beyond the workplace, however the performance environment targeted as part of this curriculum was employment-related (Lu et al, 2020;Oursler et al, 2019).…”
Section: Work-related Soft Skillsmentioning
confidence: 99%
“…3) Further developing the curriculum to become a brief, targeted intervention specifically for people with ASD would likely be useful. The curriculum and a DST training approach for work related soft skills has been effective with other populations (Oursler et al, 2019). Previous literature suggests that when working with persons with autism using cognitive behavior therapy approach, there are several ways to make CBT work for persons with autism.…”
Section: U N C O R R E C T E D a U T H O R P R O O Fmentioning
confidence: 99%
“…In other research also discussed the outplacement service for employees to improve the results in the field. There are still many of them who are more satisfied in providing professional job training as compared to the work transfer, and external outplacement usually more offer a relatively high salary, but they feel not getting emotional service (Kilcrease, 2013;Oursler, Lu, Herrick, & Harris, 2019;Rahmani, Doshmanziari, & Asgari, 2018). An employee's job satisfaction is essential to a Human Resource or a counselor.…”
Section: Introductionmentioning
confidence: 99%